(untitled) (Journal of Health, Technology and Science (JHTS), 2026)
Patient satisfaction is a critical indicator of healthcare service quality, manifesting when clinical delivery aligns with consumer expectations. This study evaluates inpatient satisfaction regarding pharmaceutical services at Prof. Dr. H. Aloei Saboe Regional General Hospital. Methods: A descriptive quantitative approach was employed, utilizing the SERVQUAL framework to assess service dimensions. Data were collected via structured questionnaires and observations from 96 respondents selected through purposive sampling. Statistical validation was conducted using the Binomial Test. Results: The analysis yielded a significance value of 0.000 (p < 0.05), leading to the rejection of the null hypothesis (H0). The findings demonstrate that 99% of respondents were satisfied, with the Tangibles dimension receiving the highest rating, while Reliability highlighted areas for inventory optimization. Conclusion: Inpatients are highly satisfied with the pharmaceutical services provided. However, sustaining this excellence requires continuous improvements in drug availability and professional responsiveness to bridge minor service gaps.